Synthesis of single-crystal La0.67Sr0.33MnO3 freestanding films with different crystal-orientation - Lu, Zengxing; Liu, Jingwu; Feng, Jiatai; Zheng, Xuan; Yang, Li-hong; Ge, Chen; Jin, Kui-juan; Wang, Zhiming; Li, Run-Wei (American Institute of Physics Inc., 2020)
We report the synthesis of single-crystal La0.67Sr0.33MnO3 (LSMO) freestanding films with different crystal orientations. By using pulsed laser deposition, water soluble perovskite-like sacrificial layers Sr3Al2O6 (SAO) followed by LSMO films are grown on differently oriented SrTiO3 substrates. Freestanding LSMO films with different orientations are obtained by etching the SAO in pure water. All the freestanding films show room-temperature ferromagnetism and metallicity, independent of the crystal orientation. Intriguingly, the Curie temperature (TC) of the freestanding films is increased due to strain relaxation after releasing from the substrates. Our results provide an additional degree of freedom to tailor the properties of freestanding perovskite oxide heterostructures by crystal orientation and an opportunity to further integrate different oriented films together.